ANALISIS PERGERAKAN TANAH BERDASARKAN PEAK GROUND VELOCITY (PGV) AKIBAT GEMPA BUMI DI LUWUK - Lingkan Mantiri Paat Timbuleng; Armstrong Sompotan; Farly R Tumimomor (Program Studi Pendidikan Fisika Jurusan Fisika Fakultas Matematika, Ilmu Pengetahuan Alam, dan Kebumian (FMIPAK), Universitas Negeri Manado, 2020)
Central Sulawesi is located between the boundaries of tectonic plates which are interconnected with one another. Some tectonic plates are located near Central Sulawesi, including the Indo-Australian plate, the Pacific plate, and the Eurasian plate. The interaction of these plates causes the formation of subduction and fault lines as locations that have the potential to become the center of an earthquake. Earthquakes at scale specific strength can cause infrastructure damage and fatalities. This has led to the importance of erecting earthquake resistant buildings based on the characteristics of ground motion which is Peak Ground Velocity and Ground Motion Prediction Equation method. The purpose of this study is to see the pattern of the relationship between Peak Ground Velocity and earthquake parameters, make an empirical equation of Peak Ground Velocity predictions and see the gorund motion in the Luwuk area with coordinate 2,5 °LS – 1,5°LU dan 119°BT - 127°BT used the Peak Ground Velocity and Ground Motion Prediction Equation method. The result shows the pattern is directly proportional to the relationship between earthquake parameters and the Peak Ground Velocity, and for the empirical equation obtained is log (PGV) = -3.8873 + 1.026975 x M – 1.34171 x log (R +17).